Economic Burden Associated with Neurocysticercosis at a Tertiary Care Neurological Center in Nepal - Acharya, Samir; Rajbhandari, Pravesh; Shrestha, Resha; Dhakal, Sudan; Shrestha, Pranaya; Gajuryal, Sharad Hari; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Introduction: Neurocysticercosis (NCC) is the most common parasitic disease of the central nervous system and is a major cause of epilepsy and neurological morbidity in humans in endemic areas of the world. This study was conducted to estimate economic burden of the paients due to Neurocysticercosis arriving at Tertiary Neurological center of Kathmandu,Nepal. Methods: A cross sectional prospective study was conducted for 2 years among the patients with NCC at Tertiary Neurological Center in Kathmandu. Patients treatment plan and followup date were recorded and patient were categorized into four different groups depending on the frequency of followup and completion of treatment(Group 1 to Group 4). Direct and indirect cost centers were catagorised and calculated accordingly. The cost was estimated in US dollar as of 2020. Results: Out of 52 patients who were followed up completely for treatment, majority of patient were from age group 21-30 years . The total cost incurred for group 1, group 2, group 3 and group 4 were 468, 714, 1054 and 1986 respectively.The average cost per day for a patient with NCC was calculated to be 1.5. Conclusion: This study suggests that Neurocysticercosis results in considerable monetary losses to patient in developing country like Nepal. The average loss of each individual accounted for around one half of per day capita income of Nepal. Various programs and poolicies shall be implemented to reduce the burden of NCC so as to reduce the economic burden associated to it.